A numerical airflow pattern study of a floor swirl diffuser for UFAD system - Yau, Yat Huang; Poh, Kai Sin; Badarudin, Ahmad (Elsevier, 2018)
Floor swirl diffuser is one of the commonly used diffusers in underfloor air distribution (UFAD) system. Geometrical design of the floor swirl diffuser will affect the airflow pattern of the indoor environment. Thus, the purpose of this study is to examine the effect of geometrical design of a floor swirl diffuser on the aspects of airflow rate, number of diffuser blades, angle of attack of diffuser blades, and the grille thickness. Laboratory experiment was carried out to validate CFD simulation results. The results of this study have shown that diffuser blades have an important role in the airflow pattern. The grille thickness, which is required to withstand the impact and the load of human and furniture, needs to be minimized as the thickness is detrimental to the function of diffuser blades. Besides, airflow rate per diffuser is studied in UFAD system in order to achieve thermal stratification. The air throw is lower compared to a high angle of attack at the low angles of attack of 30° and 45°. The optimum number of diffuser blades to create the swirl effect is 18 blades with a free area of 18.86%.